2020
DOI: 10.3856/vol48-issue1-fulltext-2300
|View full text |Cite
|
Sign up to set email alerts
|

Anisakid nematodes prevalence in Chilean hake (Merluccius gayi gayi) commercialized in the city of Talca, Chile

Abstract: The main objective of this work was to determine the presence of anisakid larvae in fresh Chilean hake Merluccius gayi gayi coming from the coastal area near the city of Talca, Chile, commonly commercialized by a regional fish supply center located in the same city. Flesh and viscera of 214 fish were analyzed via direct observation, and the prevalence of parasitism was calculated. The results showed a prevalence of 100% and 24.3% in viscera and flesh, respectively. Morphologic characterization of 138 randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…As such, anisakid prevalence in muscle resulted in rather high levels with 18.6%, 15%, and 1.7% in Chilean hakes, snoeks, and sea breams, respectively. Prevalence of anisakid larvae in muscles of Chilean hakes has also been reported high reaching values of 24.3% (Silva et al 2020) and 32% (Madrid et al 2016) in Central-Southern regions and 29.2% in Southern regions of the country (Torres et al 2000a, b) being relatively similar to our data. Conversely, prevalence of anisakid larvae in muscle tissue of snoeks and sea breams has scarcely been studied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, anisakid prevalence in muscle resulted in rather high levels with 18.6%, 15%, and 1.7% in Chilean hakes, snoeks, and sea breams, respectively. Prevalence of anisakid larvae in muscles of Chilean hakes has also been reported high reaching values of 24.3% (Silva et al 2020) and 32% (Madrid et al 2016) in Central-Southern regions and 29.2% in Southern regions of the country (Torres et al 2000a, b) being relatively similar to our data. Conversely, prevalence of anisakid larvae in muscle tissue of snoeks and sea breams has scarcely been studied.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, composition of endoparasite fauna in marine organisms, including fish, is mainly influenced by their feeding habits (predator-prey relationships; Chavez et al 2012). In Chile, fish preys of snoeks and Chilean hakes have also been reported to be infected with anisakid larvae indicating that these two piscivorous species could clearly act as paratenic hosts in epizootiology of anisakiasis (Valdivia et al 2007;George-Nascimento and Moscoso 2013;Silva et al 2020) being also trophically transmitted among diverse marine species (Valdivia et al 2007). More importantly, Chilean hakes are one of the main pray fish of South American sea lions (Otaria flavescens) in this region, thereby probably representing a pivotal role transmission routes of anisakiasis (George-Nascimento and Llanos 1995; González-Saldía et al 2015) and contributing to the perpetuation of life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In Italian waters, Dezfuli et al (2015) described the infection of Perca fluviatilis L. musculature with Eustrongylides sp. Silva et al (2020), Madrid et al (2016), andTorres et al (2014) all reported the presence of Anisakis spp. and Pseudoterranova spp.…”
Section: Discussionmentioning
confidence: 96%
“…De esta forma, es necesario reforzar la compra del pescado eviscerado, el hábito de consumir el pescado previa cocción sobre 63 °C por 10 a 15 minutos, o bien, congelación rápida a temperaturas inferiores a -20 °C durante siete días o -35 °C por 24 horas, procedimientos que permiten matar a las larvas (Adams y cols., 2005; Sánchez-Monsálvez y cols., 2006) 25,26 , y que el salado, ahumado o sometimiento a horno microonda de la carne de pescado no son larvicidas (de la Torre y cols., 2000) 27 . Así mismo, sugerimos preferir cocinar solo la musculatura epiaxial del pez, lugar de menor frecuencia de localización de larvas de anisákidos, tal como se evidencia en nuestro estudio, así como en otros similares (Madrid, y cols., 2016; Silva y cols., 2020) 13,28 .…”
Section: Artículo De Investigaciónunclassified